2022
DOI: 10.1001/jamaoto.2022.2561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optimal Assessment Schedules for Surveillance After Definitive Locoregional Treatment of Locally Advanced Head and Neck Cancer

Abstract: ImportanceIn clinical practice, assessment schedules are often arbitrarily determined after definitive treatment of head and neck cancer (HNC), producing heterogeneous and inconsistent surveillance plans.ObjectiveTo establish an optimal assessment schedule for patients with definitively treated locally advanced HNC, stratified by the primary subsite and HPV status, using a parametric model of standardized event-free survival curves.Design, Setting, and ParticipantsThis was a retrospective study including 2 ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…For example, in South America, >60% of throat cancer patients are associated with smoking and drinking habits (6,9,10). In addition, recent studies have detected human papillomavirus (HPV) infection in approximately 20-30% of laryngeal cancer patients and may be associated with survival in laryngeal cancer patients (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in South America, >60% of throat cancer patients are associated with smoking and drinking habits (6,9,10). In addition, recent studies have detected human papillomavirus (HPV) infection in approximately 20-30% of laryngeal cancer patients and may be associated with survival in laryngeal cancer patients (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this model, optimal follow-up schedules varied widely. 2 For HPV + oropharyngeal carcinoma, follow-up was recommended every 7.1 months in the first phase and even less often in later phases, whereas for hypopharyngeal carcinoma, follow-up was recommended every 2.1 months in the first phase and continued being quite intensive in the later phases. Overall, survivors of HPV + oropharyngeal cancer required only 4 additional surveillance visits during 8 years after the initial 6-month posttreatment period, whereas survivors of hypopharyngeal cancer required 15 visits.…”
mentioning
confidence: 99%
“…These limitations aside, parametric piecewise exponential modeling has shown promise (as the authors noted) for glioma surveillance 2 ; other studies have shown its potential for use in studying breast cancer and melanoma outcomes. 3,4 However, to our knowledge, no study has validated parametric modeling in head and neck cancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations